Poetas en la España leal : Antonio Machado, Rafael Alberti, Manuel Altolaguirre, Luis Cernuda, Juan Gil-Albert, Miguel Hernández, León-Felipe, José Moreno Villa, Emilio Prados, Arturo Serrano Plaja y Lorenzo Varela / [Manuel Aznar Soler, pr.] - Machado, Antonio (1875-1939) Alberti, Rafael (1902-1999) Altolaguirre, ManuelCernuda, Luis (1902-1963) Gil-Albert, Juan (1904-1994) Hernández, Miguel (1910-1942) León Felipe (1884-1968) Moreno Villa, José (1887-1955) Prados, Emilio (1899-1962) Serrano-Plaja, Arturo (1909-1979) Varela, LorenzoAznar Soler, Manuel
Prólogo: Poesía, Guerra y Revolución en cuadernillo anexo